Identification of Potential Local Food Ingredients as a Food Source for Stunting Prevention in Langkat District - Eka Febriyanti; Leylia Khairani; Siti Hajar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Stunting is a child nutrition problem that is an important concern in Indonesia because of the large number of complications it causes, such as impaired growth and development, cognitive problems, decreased immune system, risk of metabolic disease and socio-economic problems. Indonesia's stunting prevalence is high, still above 20% (21.6%). Langkat Regency has the potential for local food ingredients that can meet the nutritional needs of families so as to prevent malnutrition and stunting. The aim of this community service is to identify the potential of local food ingredients. The method used was a Focus Group Discussion with relevant stakeholders in Langkat Regency. From the results of the discussion, it was found that the potential for local food ingredients were rice, fish, vegetables and local fruit such as bananas, rambutan and papaya. Furthermore, training is needed to process the available food sources so that they are highly nutritious and affordable for the community.